دور وسائل التواصل الاجتماعي في التأثير على مراحل عملية الشراء دراسة ميدانية على عملاء شركات الاتصالات الخليوية السورية - قاسم سامر; ديوب جودت (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تزايد اهتمام الباحثين بتأثير وسائل التواصل الاجتماعي على عملية الشراء من خلال دراسة العديد من العوامل الثقافية المؤثرة في سلوك المستهلك، والتي تتغير تبعاً للتطورات التكنولوجية المتسارعة، وتبني المستهلكين للتكنولوجيا في ممارسة أنشطتهم التجارية بشكل مطرد؛ حيث تتجه إدارة العلاقات العامة في المنظمات المختلفة إلى تبني وسائل التواصل الاجتماعي كوسيلة تفاعلية تسهل على المنظمات بناء قواعد بيانات دقيقة عن عملائها، وتتيح لها سهولة الوصول إليهم والتأثير في سلوكهم الشرائي. هدف البحث إلى دراسة العلاقة بين استخدام عملاء شركات الاتصالات الخليوية السورية لوسائل التواصل الاجتماعي (فيسبوك) لأغراض تسويقية، وقدرتها على التأثير في العملاء في كل مرحلة من مراحل عملية الشراء التي تتضمن: مرحلة توليد الحاجة، مرحلة البحث عن البدائل، مرحلة تقييم البدائل، مرحلة اتخاذ قرار الشراء، ومرحلة ما بعد الشراء. ولتحقيق ذلك تمّ صياغة فرضية رئيسة يتفرع عنها خمس فرضيات فرعية، واستخدم الباحث أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار الارتباط الثّنائي Pearson Correlation. وقد توصل الباحث إلى عدّة نتائج أهمّها: وجود علاقة إيجابية قوية بين استخدام عملاء شركات الاتصالات الخليوية السورية لوسائل التواصل الاجتماعي (فيسبوك) لأغراض تسويقية، وجميع مراحل عملية الشراء. Researchers have become increasingly interested in the impact of social media on the purchase process by studying many of the cultural factors influencing consumer behavior that are changing according to the rapid technological developments and the adoption of technology by consumers in the conduct of their business activities. As an interactive tool that makes it easier for organizations to build accurate databases about their customers, accessibility and impact on their purchasing behavior. The study aimed to study the relationship between the use of the Syrian mobile telecommunications companies’ customers for social media (Facebook) for marketing purposes, and their ability to influence customers at each stage of the purchase process, which includes:: the generation phase of the need, the stage of the search for alternatives, the stage of evaluating the alternatives, the stage of making the purchase decision, and the post-purchase phase. In order to achieve this, a main hypothesis was formulated with five sub-hypotheses. The researcher used the questionnaire technique to collect the data analyzed using statistical tests, the most important being the one-sample T. test and the Pearson Correlation test. The researcher has reached several results, the most important of which is: There is a strong positive correlation between the use of the Syrian mobile telecommunications companies’ customers for social media (Facebook) for marketing purposes and all stages of the purchase process.